Improving the Students' Creative Thinking Skills Through The Implementation of Controversy – Based Integrated Science Learning Tools - Sudarto, Sudarto; Jauhar, Sitti; Rosmalah, Rosmalah; Muliadi, Muliadi; Mujahidah, Mujahidah (Universitas Negeri Makassar, 2021)
This study aimed to measure the improvement of students' creative thinking skills after using Controversy-based integrated science learning tools. The study employed a pre-experimental design with one group pretest-posttest. The research subjects were 20 students of the Science Education Program, The State University of Makassar selected using the Nonprobablit sampling technique (saturation sampling). The instrument was an essay test that had been validated. The findings show a significant difference in students' average creative thinking skills before and after learning using Controversy based Integrated Science learning tools. It shows that the improvement of students' creative thinking skills after being treated with Controversy based Integrated Science learning tools was in high category and significant. Students were able to develop their knowledge, predict some limited information, formulate a solution to a problem, and analyze information from different perspectives.